2019
DOI: 10.1002/ecy.2641
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical recuperation of lowland tropical forest during succession

Abstract: 2019. Biogeochemical recuperation of lowland tropical forest during succession. Ecology 100(4):Abstract. High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 101 publications
(250 reference statements)
2
26
0
Order By: Relevance
“…Additionally, N rapidly recovers after disturbance in the Central Congo basin due to the active biological nitrogen fixation in the early successional stages (Bauters et al, 2016) and the deposition of high amounts of exogenous nitrogen in older forests (Bauters et al, 2018). Leaf phosphorus slightly increased from 5 years to 60 years and then decreased in OG, while canopy N:P initially decreased (5-12 years) before it increased again, suggesting increasing P limitation for the most advanced successional stages (Sullivan et al, 2019).…”
Section: Recovery Of Functional Diversity and Compositionmentioning
confidence: 99%
“…Additionally, N rapidly recovers after disturbance in the Central Congo basin due to the active biological nitrogen fixation in the early successional stages (Bauters et al, 2016) and the deposition of high amounts of exogenous nitrogen in older forests (Bauters et al, 2018). Leaf phosphorus slightly increased from 5 years to 60 years and then decreased in OG, while canopy N:P initially decreased (5-12 years) before it increased again, suggesting increasing P limitation for the most advanced successional stages (Sullivan et al, 2019).…”
Section: Recovery Of Functional Diversity and Compositionmentioning
confidence: 99%
“…Although prescribed burns are generally of low intensity (Huang et al 2013), the loss of N through volatilisation during the fire is (Guinto et al 2001;Reverchon et al 2012). Several studies have demonstrated the constraining nature of N in forest post-disturbance recovery (Davidson et al 2004;Amazonas et al 2011;Sullivan et al 2019) and the importance of N 2 -fixing species to relieve this N deficiency (West et al 2005). Batterman et al (2013) showed that BNF could overcome the N limitation created by the fast plant growth occurring during secondary succession, through a feedback mechanism between postdisturbance forest regrowth and BNF.…”
Section: Discussionmentioning
confidence: 99%
“…Forest is the dominant component of the earth's biogeochemical system, which provides critical refuge for terrestrial biodiversity [1,2]. Accurate and up-to-date forest cover information is considered an important parameter to help humans to protect, conserve, monitor, and sustainably manage forests and ensure their ecological functions [3].…”
Section: Introductionmentioning
confidence: 99%
“…To help end-users to select their specific forest datasets, this study aims to evaluate the accuracy, consistency, and discrepancies of eight forest datasets in Myanmar (i.e., Hansen2010, CCI-LC2015, FROM-GLC2015/2017, FROM-GLC10, GLC-FCS2015/2020, and GlobeLand30-2020). Specifically, (1) we provide accuracy assessment by comparison with sample points collected from multi-temporal high-resolution images on Google Earth (GE);…”
Section: Introductionmentioning
confidence: 99%